Association between laryngopharyngeal reflux and benign vocal folds lesions: A systematic review. (20th March 2019) - Lechien, Jerome R.; Saussez, Sven; Nacci, Andrea; Barillari, Maria Rosaria; Rodriguez, Alexandra; Le Bon, Serge D.; Crevier‐Buchman, Lise; Harmegnies, Bernard; Finck, Camille; Akst, Lee M.
Abstract : Objectives: To investigate the role of laryngopharyngeal reflux (LPR) in the development of benign lesions of the vocal folds (BLVF). Methods: PubMed, Cochrane Library, and Scopus were searched by three independent investigators for articles published between January 1990 and November 2018 providing substantial information about the role of LPR in the development of nodules, polyps, cysts, Reinke's edema, and sulcus vocalis. Inclusion, exclusion, diagnostic criteria and clinical outcome evaluation of included studies were analyzed using Preferred Reporting Items for Systematic Reviews and Meta‐Analyses criteria. Results: Of the 155 relevant publications, 42 studies were included. Thirty‐five were clinical studies and seven were experimental research studying the impact of reflux on vocal fold tissue. Only seven clinical studies utilized objective LPR diagnoses (pH monitoring), suggesting an association between LPR and the development of nodules, polyps, and Reinke's edema. These studies were characterized by a substantial heterogeneity due to discrepancies in inclusion/exclusion criteria, diagnostic methods, and clinical outcome evaluation. The few basic science studies on this topic support that LPR creates an environment that may predispose to BLVF through changes in defense mechanisms of the vocal folds, cell‐to‐cell dehiscence, inflammatory reaction of the vocal folds, and reaction to phonotrauma. Conclusions: Caustic mucosal injury from LPR could cause increased susceptibility of the vocal fold mucosa to injury and subsequent formation of nodules, polyps, or Reinke's edema. However, the heterogeneity and the low number of high‐quality studies limit the ability to draw definitive conclusions. Future clinical and experimental studies are needed to better identify the role of reflux in development of BLVF. Laryngoscope, 129:E329–E341, 2019